Implementation of Bruner's Theory to Improve Understanding of the Concept of Numbers for Grade I Students at SDN 1 Kepanjen - Sigit Wibowo; Pujianah Pujianah; Arief Rahman Hakim; Cicilia Ika Rahayu Nita; Sigit Wibowo; Pujianah Pujianah; Arief Rahman Hakim (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Abstract: Understanding the concept is a basic ability that must be possessed by students in understanding mathematics. This study aims to determine the increase in elementary school students' conceptual understanding after applying Bruner's theory in learning mathematics. This type of research is Class Action Research. The research design used was developed by Kemmis and McTaggart where each activity cycle consists of four components, namely planning, implementation of action/treatment, observation, and reflection. The subjects in this study were 25 students of class IA SD Negeri 1 Kepanjen. The research results show that the application of Bruner's learning theory can activate students in learning. Improvement in understanding the ability of the concept occurs in each cycle. At the beginning of the observation, the average number of concept understanding abilities of students was 22.67 percent, then increased in cycle I by 44 percent, cycle II by 69.33 percent, and achieving expectations in cycle III by 88 percent. The successful application of Bruner's learning theory is also evidenced by the increased mastery of student learning outcomes. At the beginning of the cycle, only 28 percent of students passed, then increased in cycle I by 48 percent of students, cycle II by 72 percent of students, and achieving expectations in cycle III by 92 percent. Thus, the implementation of Bruner's theory can improve understanding of the concept of numbers in learning mathematics. s learning theory is also evidenced by the increased mastery of student learning outcomes. At the beginning of the cycle, only 28 percent of students passed, then increased in cycle I by 48 percent of students, cycle II by 72 percent of students, and achieving expectations in cycle III by 92 percent. Thus, the implementation of Bruner's theory can improve understanding of the concept of numbers in learning mathematics. s learning theory is also evidenced by the increased mastery of student learning outcomes. At the beginning of the cycle, only 28 percent of students passed, then increased in cycle I by 48 percent of students, cycle II by 72 percent of students, and achieving expectations in cycle III by 92 percent. Thus, the implementation of Bruner's theory can improve understanding of the concept of numbers in learning mathematics. Abstrak: Pemahaman konsep merupakan suatu dasar kemampuan yang harus dimiliki oleh siswa dalam memahami pelajaran matematika. Penelitian ini bertujuan untuk mengetahui peningkatan pemahaman konsep siswa sekolah dasar setelah diterapkan teori Bruner dalam pembelajaran matematika. Jenis penelitian ini adalah Penelitian Tindakan Kelas (classroom action research). Desain penelitian yang digunakan yaitu dikembangkan oleh Kemmis dan Mc Taggart dimana tiap-tiap siklus kegiatan terdiri atas empat komponen yaitu perencanaan (plan), pelaksanaan tindakan/perlakuan (action), observasi (observation), dan refleksi (reflection). Subjek dalam penelitian ini yaitu siswa kelas IA SD Negeri 1 Kepanjen yang berjumlah 25 siswa. Hasil penelitian menunjukkan bahwa penerapan teori belajar Bruner dapat mengaktifkan siswa dalam pembelajaran. Peningkatan kemampuan pemahaman konsep terjadi pada setiap siklus. Pada awal observasi, rata-rata kemampuan pemahaman konsep bilangan pada siswa sebesar 22,67 persen, kemudian meningkat pada siklus I sebesar 44 persen, siklus II sebesar 69,33 persen, dan mencapai harapan pada siklus III sebesar 88 persen. Keberhasilan penerapan teori belajar Bruner juga dibuktikan dengan meningkatnya ketuntasan hasil belajar siswa. Pada awal siklus, hanya sebanyak 28 persen siswa yang tuntas, kemudian meningkat pada siklus I sebesar 48 persen siswa, siklus II sebanyak 72 persen siswa, serta mencapai harapan pada siklus III sebesar 92 persen. Dengan demikian, implementasi teori Bruner dapat meningkatkan pemahaman konsep bilangan pada pembelajaran matematika.